Desenvolvimento e validação de metodologias para avaliação de ezetimiba por cromatografia líquida e espectrometria de massas - Oliveira, Paulo Renato de (2007)
Ezetimibe selectively inhibits the intestinal absorption of dietary cholesterol and related plant sterols, from the 2-azetidinones group, and is used for the treatment of hypercholesterolemia and phytosterolemia. The methodologies for the evaluation of ezetimibe in pharmaceutical products and plasma were developed and validated in the present work. The reversed-phase liquid chromatography (RP-LC) analysis was carried out using a Synergi fusion C18 column (150 mm x 4.6 mm), maintained at 45 oC. The mobile phase consisted of potassium phosphate buffer 0.03 M, pH 4.5/acetonitrile (35:65, V/V), run at a flow rate of 0.6 mL/min with detection at 234 nm. The chromatographic separation was obtained within 15 min and it was linear in the concentration range of 0.5-200 Hg/mL. The method was sucessfuly applied for the simultaneous determination of ezetimibe and simvastatin in pharmaceutical products. The liquid chromatography-tandem mass spectrometry (LCMS/ MS) method was developed and validated using a Luna C18 column (50 mm x 3.0 mm) and the mobile phase consisted of acetonitrile:water (85:15, V/V), run at a flow rate of 0.4 mL/min. The mass spectrometer, equipped with electrospray positive source, was used in multiple reaction monitoring mode (MRM), monitoring the transitions of 392.0>161.0 and 359.3>280.0, for ezetimibe and etoricoxib (internal standard), respectively. The chromatographic separation was obtained within 2 min and it was linear in the concentration range of 0.25-20 ng/mL (ezetimibe) and 1-300 ng/mL (ezetimibe and its glucuronide matabolite). The procedures were validated evaluating parameters such as the specificity, linearity, precision, accuracy, robustness, limit of detection and limit of quantitation. Besides, for the bioanalytical method, the matrix effects, recovery and stability studies were also analyzed, giving results within the acceptable range. The proposed method was applied for the analysis of pharmaceutical products, showing significant correlation (P>0.05) of the results. Moreover, the liquid-liquid extraction method developed and optimized allowed high mean recoveries of ezetimibe and internal standard from the plasma samples. The procedures can be applied for the biovailability studies and for the quality control of pharmaceutical products.